Effectiveness of biofertilizer formula on soil chemical properties and shallot productivity in tidal swamp land. Issue 1 (February 2021) - Mukhlis,; Lestari, Y; Yufdy, M P; Razie, F
Abstract: Low productivity is one of the main problems to increase shallot productivity in tidal swamp lands. Biofertilizer is an alternative to increase soil fertility, plant productivity, inorganic fertilizer efficiency, and decrease environmental pollution. The aim of this research was to test the biofertilizer formula containing decomposer ( Trichoderma sp ), P-solubilizer ( Bacillus sp ), and N-fixer ( Azospirillium sp and Azotobacter sp ) to increase soil chemical properties and shallot productivity in tidal swamp lands. This research was conducted from July – September 2018 in Wanaraya District, Barito Kuala Regency, South Kalimantan. The treatments involved (A) No fertilizer, (B) NPK (recommendation dose), (C) Biofertilizer, (D) Biofertilizer + NPK (50% of recommended dose), (E) Biofertilizer + NPK (75% of recommended dose). The treatment was arranged by randomized completely block design with four replications. Recommended dose of NPK fertilizer was NPK compound 500 kg ha −1, SP-36 150 kg ha −1, dan KCl 200 kg ha −1 . Research results showed that biofertilizer formula combined by inorganic NPK fertilizer as much as 50 to 75 % of recommended dose could increase soil chemical properties and yielded as much as 2.39 to 6.19% compared to NPK fertilizer with recommended dose. For further development, this biofertilizer need to be tested at several locations with broader plot size.